A practice-oriented perspective on collaborative creative design. Issue 3 (1st October 2016) - Richter, Christoph; Allert, Heidrun
Abstract: Even though there has been a considerable interest in creativity and design as collaborative efforts more recently, there is yet a need for models that provide an integrative perspective on collaborative creative design. While cognitivist accounts of creativity are still quite dominant in the field of design research, it is argued in this article that respective models fall short of accounting for the emergent properties and structures that arise out of the interaction of human actors with their environment. To be able to account for the social and material contingencies out of which different forms of creative design take shape, a practice-oriented perspective is explicated and its implications are discussed. The intent of this article is to open up a new research agenda that helps to understand how creative practices take shape and are enacted in specific settings.